The use of interactive multimedia website in learning basic Japanese / Muhammad Alif Redzuan Abdullah and Sanimah Hussin - Redzuan Abdullah, Muhammad Alif; Hussin, Sanimah (2019)
Japanese language is one of the most popular foreign languages studied as a major or elective by students in Universiti Putra Malaysia (UPM). The learning of Japanese language focuses on four skills: listening, speaking, reading, and writing. In order to achieve competency in these four language skills, it is important for learners to first master a sufficient number of Japanese vocabulary items. This research was conducted with an aim to explore and gather information on the needs of an interactive multimedia website for the acquisition of Japanese vocabulary and grammar in UPM. The research applied a qualitative data collection method that focused on interview and observation. An interactive multimedia website was developed to enable users to learn basic Japanese words and grammar using an e-learning platform application which incorporates various multimedia tools such as animation, songs, graphic, movies, and the Internet that might prove to be successful in turning traditional classrooms into communicative and student-centered classrooms. The results of the research indicates the need for an interactive multimedia website in learning the Japanese language in order to make vocabulary and grammar learning interesting, apart from facilitating independent learning among Japanese language learners in UPM.